A high-temperature passaging attenuated Pseudorabies vaccine protects piglets completely against emerging PRV variant. (June 2017) - Liang, Chao; Tong, Wu; Zheng, Hao; Liu, Fei; Wu, Jiqiang; Li, Guoxin; Zhou, En-min; Tong, Guangzhi
Abstract: Emerging variant of pseudorabies virus (PRV) have evaded the antiviral immunity of commercially available PRV vaccine and have led to PRV outbreaks in Chinese pig farms. Here, we attenuated a PRV variant strain by serial passages in vitro and evaluate the protective efficacy of the attenuated strain as a vaccine candidate. The virulent PRV variant strain JS-2012 was continuously passaged in Vero cells at 40 °C and attenuated rapidly. After 90 passages in Vero cells, the passaged virus lost its ability to cause death in 2-week-old piglets. The 120th passage virus was avirulent in the sucking piglets. An attenuated strain, JS-2012-F120 derived from the 120th passage virus by three rounds of plaque cloning grew better than its parent strain JS-2012 in Vero cells and showed notably different cytopathic effects and plaque morphology from JS-2012. PCR combined with sequence analysis showed that JS-2012-F120 contained a 2307-bp deletion covering nucleotide 487 of gE gene to 531 of US2 gene. After inoculation with JS-2012-F120, young piglets were completely protected from challenge with the classical and emerging virulent PRVs. Moreover, the piglets did not develop specific gE antibodies. Thus, JS-2012-F120 appears to be a promising marker vaccine to control PRV variant circulating in Chinese pig farms, and the high-temperature passaging in vitro was an efficient method to attenuated alphaherpesvirus. Highlights: A virulent Pseudorabies virus variant strain JS-2012 was rapidly attenuated by high-temperature passaging in vitro. The attenuated strain JS-2012-F120 contained a deletion covering gE to US2 and grew better than JS-2012 strain in Vero cells. JS-2012-F120 provided full protection for piglets against challenge of the virulent PRV variant and induce no gE antibodies.